The little liar ebook A novel. - Albom, Mitch (2023)
An Instant New York Times Bestseller Beloved bestselling author Mitch Albom returns with his most important novel to date, an unforgettable story of truth and lies set during the Holocaust. Eleven-year-old Nico Krispis has never told a lie. When the Nazis invade his home in Salonika, Greece, the trustworthy boy is discovered by a German officer, who offers him a chance to save his family. All Nico has to do is persuade his fellow Jewish residents to board trains heading "north," where new jobs and safety await. Unaware that this is all a cruel ruse, the innocent boy reassures passengers on the station platform every day. But when the final train is loaded, Nico sees his family being herded into a boxcar. Only then does he discover that he has helped send them—and everyone he knows and loves—to their doom at Auschwitz. Nico escapes—but he never tells the truth again. In The Little Liar, Mitch Albom examines the human repercussions of deception by interweaving the stories of Nico, who yearns for forgiveness; his older brother, Sebastian, who vows revenge against him; Fannie, the girl who must choose between them; and Udo Graf, the Nazi officer who forever changed their lives with his lies. Through the war years, the concentration camps, and the decades that follow, Albom reveals the consequences of each person's honesty and dishonesty, bringing them back to where it all started in a staggering climax worthy of the best of Albom's internationally embraced stories.